2013
DOI: 10.1007/s10955-013-0760-6
|View full text |Cite
|
Sign up to set email alerts
|

The Fermi-Pasta-Ulam Problem and Its Underlying Integrable Dynamics

Abstract: This paper is devoted to a numerical study of the familiar α+β FPU model. Precisely, we here discuss, revisit and combine together two main ideas on the subject: (i) In the system, at small specific energy ε = E/N, two well separated time-scales are present: in the former one a kind of metastable state is produced, while in the second much larger one, such an intermediate state evolves and reaches statistical equilibrium. (ii) FPU should be interpreted as a perturbed Toda model, rather than (as is typical) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
157
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(167 citation statements)
references
References 27 publications
9
157
1
Order By: Relevance
“…In ref. 4, it has been shown that the α-FPU can be seen as a perturbation of the integrable Toda lattice (see also ref. 27).…”
Section: Relation To the Toda Latticementioning
confidence: 99%
See 2 more Smart Citations
“…In ref. 4, it has been shown that the α-FPU can be seen as a perturbation of the integrable Toda lattice (see also ref. 27).…”
Section: Relation To the Toda Latticementioning
confidence: 99%
“…More recently, very long numerical simulations have shown clear evidence of the phenomenon of equipartition (see, for instance, ref. 4 and references therein). However, despite substantial progress on the subject (5-10), to our knowledge no complete understanding of the original problem has been achieved so far, and the numerical results of the original α-FPU system remain largely unexplained from a theoretical point of view.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the energy transport behaviors of Toda model have been found very similar to the FPU model in the short time scale [21,22,24]. But the difference is also obvious.…”
Section: Introductionmentioning
confidence: 76%
“…Since then, extensive studies on the energy transport behaviors in nonlinear lattices have been carried out . For the FPU model, there is a general agreement that two well separated time scales are present for weak nonlinearity [15,[20][21][22]24]. That is, in a relative short time scale, a kind of metastable state is appeared.…”
Section: Introductionmentioning
confidence: 88%